A simple unconstrained semi-continuous model for calculating likelihood ratios for complex DNA mixtures. (December 2015) - Russell, Daniel; Christensen, William; Lindsey, Todd
Abstract: Methods for calculating likelihood ratios to provide weight for complex DNA mixtures have been developed, but factors including the complexity of the equations and assumptions about the possible number of contributors to a profile have prevented some laboratories from embracing these methods. By producing and studying complex DNA mixture profiles and approaching interpretation using a minimal number of assumptions, we have developed a semi-continuous method for calculating likelihood ratios. The unconstrained likelihood ratio (UCLR) model for providing statistical weight to inclusions is simple and can be performed without making assumptions about the number of contributors. Additionally, we are able to establish and test the limits of the model, providing greater assurance that false inclusions will not occur by chance.